The Alternative Electrical Properties of (Al -CdSe0.8Te0.2Al) Capacitor at Room Temperature - Ibraheem, G.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research aims to prepare an (Al-CdSe0.8Te0.2-Al) capacitor and study the alternating electrical properties of it at room temperature, and study the possibility of using these films in electronical applications. The A.C. conductivity of as-deposited films have been measured in the frequency range (f =100Hz-400KHz), and it has shown that A.C. conductivity ( Ïƒa.c ) increases with the frequency increasing. The study of the variation of each of the capacitance and real part of the dielectric constant (Ð„r ) with frequency has shown that their values decrease with frequency increasing. The study of the variation of each of the imaginary part of dielectric constant (Ð„i ) and the loss factor with frequency has shown that their values decrease with frequency increasing and then they began to increase.